The likeness in Aristotle - Cárdenas Mejía, Luz Gloria (Estudios de Filosofía, 1996)
This paperpurports to show how the notion of resemblance plays an important role, in the construction of various disciplines, and therefore in the Concept-making processes that structure them. An overview of the different ways of concept-formation will be presented,for the purpose of establishing the uses that this notion has been going through. The relevance of Concept-formation in the production ofknowledge, and that of through processes in establishing resemblance are remarked here. Finally, reference is made ofthe reflections this way ofworking provokes in two contemporary philosophers, Gadamer and Ricoeur.